1995
DOI: 10.1161/01.str.26.7.1231
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Ulceration and Lumen Thrombus Are the Main Sources of Cerebral Microemboli in High-grade Internal Carotid Artery Stenosis

Abstract: We conclude that ulceration and luminal thrombosis of the atheromatous plaque are the main sources of downstream cerebral microemboli in patients with high-grade internal carotid artery stenosis. Our data support the view that these pathoanatomic features may also play a key role in symptom development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
223
3
21

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(252 citation statements)
references
References 19 publications
5
223
3
21
Order By: Relevance
“…16 -19 Falk 16 noted that Ͼ75% of major coronary thrombotic events were precipitated by atherosclerotic plaque rupture, which resulted in the exposure of thrombogenic subendothelial plaque constituents. Falk and other researchers [17][18][19] suggested that plaque disruption and erosion was the critical feature in these moderately stenotic, high-risk lesions. MRI can detect FC status (thick, thin, and ruptured) ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…16 -19 Falk 16 noted that Ͼ75% of major coronary thrombotic events were precipitated by atherosclerotic plaque rupture, which resulted in the exposure of thrombogenic subendothelial plaque constituents. Falk and other researchers [17][18][19] suggested that plaque disruption and erosion was the critical feature in these moderately stenotic, high-risk lesions. MRI can detect FC status (thick, thin, and ruptured) ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies provide evidence that TCD detectable microembolic signals indicate a risk factor for cerebral ischemia. [15][16][17] Although the nature of the detected signals cannot be clearly identified, eg which aggregates of blood cells generate the signal, the method seems to be sensitive for blood inhomogeneity. The fact that after stimulation donors presented signs of hypercoagulation but no microembolism is compatible with the known clinical low incidence of ischemic morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Plaque ulceration has been defined as "an intimal defect larger than 1000-m in width, exposing the necrotic core of the atheromatous plaque." 14 Conventional angiography has been considered the standard method for evaluating stenosis of the carotid artery, but it is not sufficiently reliable for detecting plaque ulceration 15,16 (angiography has a 46% sensitivity and a 74% specificity for detecting ulcerated plaques in large studies 17,18 ). Moreover, conventional angiography is also associated with an increased risk of thromboembolic events.…”
mentioning
confidence: 99%